Malaysian Chinese Stories Of Hard Work: Folklore And Chinese Work Values - See , Hoon (Penerbit Universiti Sains Malaysia (USM Press), 2015)
The Chinese, especially overseas Chinese and particularly the Malaysian Chinese, are well known for being hardworking and for their economic success. A certain degree of stereotyping is present here, of course, but Chinese success stories are certainly inspirational. This article demonstrates that Chinese folk narratives may have contributed to moulding the hardworking and entrepreneurial characteristics of the Chinese. Folklore, particularly folk narrative, plays a number of functions in non-literate societies, such as entertainment, validation of culture and the transmission of values. One of the major functions of folklore in non-literate societies is value transmission. In a modern society, folklore can perform the same function, although the transmission may be in the form of a book or a digital animation. To attempt to "scientifically" show that the Malaysian Chinese are likely to be influenced by these materials, this study analyses folk narratives that are commonly available in Chinese children's textbooks used in Chinese primary schools. The tales transmit values such as diligence, determination (especially in learning), loyalty, creativity, courage and to some extent, shrewdness, which are important to economic success.